Dieta hiperlipídica e hipernatremia: alterações autonômicas e cardiovasculares - Amaral, Nathalia Oda (2018)
Hypertension is the most common pathologies which affect population. Of the factors that can promote hypertension, food behavior is highlighted in relation to unhealthy eating habits present in western diet. Thus, present study sought to evaluate some aspects of this pathology in several situations, and themes were discussed separately in two chapters. In the first moment, effect of maternal hyperlipidic diet on metabolic and autonomic parameters in offspring was evaluated. It is known which obesity induced by maternal diet can modify central regulatory pathways of the fetus, mainly long-term regulation of appetite, but no work sought to evaluate the influence of the maternal hyperlipidic diet (HD) on cardiovascular and autonomic parameters in the offspring . Female Holtzman rats (280-300 g) were divided into two groups. One group received standard diet (SD) and other HD. The animals had free access to SD or HD for 6 weeks prior and during gestation and lactation period. All pups were weaned after 21 days of life and had free access to SD. After one week some offspring and mothers were submitted to glycemic test and later euthanized for removal of adipose tissue and blood. Other offspring were submitted to in situ preparation. DH increased adipose tissue in all females, but was able to change only metabolic triacylglycerols concentration. Offspring of HFD dams (OffHFD) showed an increase in adipose tissue and total cholesterol and HDL levels. Offspring of SD dams (OffSD) showed decrease in sympathetic activity after pre-colicular transection. This effect was not observed in males offspring of mothers with HFD (OffHFD). KCN infusion caused similar increases in abdominal activity (ABD), in phrenic nerve frequency (PNA f) and sympathetic activity (SNA), but in OffHFD this increase in SNA was smaller. KCN caused increase in phrenic nerve amplitude (PNA) and was higher in OffHFD. Hypercapnia resulted in increase in SNA, ABD and PNA and decrease in PNA f in both groups. The decrease in PNA f was more pronounced in OffHFD and increased PNA was higher in OffHFD. Phenylephrine caused in both groups decrease in SNA, ABD and PNA, and generated an increase in PNA f. The reduction of SNA was higher in OffHFD. These results suggest that maternal HFD during fetal development alters central connections in offspring. In second moment oxytocin effects on vascular reactivity and its role in hypernatremia-induced responses were evaluated. Changes in volume and/or extracellular compartments composition are known to evoke various autonomic, cardiovascular and hormonal responses that to modulate renal excretion of water and sodium. The main vegetative adjustments are: renal vasodilation and oxytocin secretion. Regulation of osmolarity and volume is critical for survival. Despite knowledge, no study evaluated interaction between renal sympathetic activity and oxytocin secretion on renal and cardiovascular responses induced by sodium overload. Male Wistar rats (280–350 g) were anesthetized with sodium thiopental (40 mg/kg, i.v.). Animals were also instrumented for measurement of mean arterial pressure (MAP) and renal blood flow (RBF). Renal vascular conductance (RVC) was calculated as the ratio of RBF by MAP. In anesthetized rats (n = 6), OT infusion (0.03 μg/kg, i.v.) induced renal vasodilation. Ex vivo experiments demonstrated that OT caused renal artery relaxation. Blockade of OT receptors (OTR) reduced these responses to OT, indicating a direct effect of this peptide on OTR on this artery. Hypertonic saline (3 M NaCl, 1.8 ml/kg b.wt., i.v.) was infused over 60 s. In sham rats (n=6), hypertonic saline induced renal vasodilation. The OXTR antagonist (AT; n=7) and renal denervation (RX) reduced the renal vasodilation induced by hypernatremia. Atosiban with renal denervation (RX+AT; n=7) completely abolished renal vasodilation induced by sodium overload. Intact rats excreted 51% of the injected sodium within 90 min. Natriuresis was slightly blunted by atosiban and renal denervation (42% and 42% of load, respectively), whereas atosiban with renal denervation reduced sodium excretion to 16% of the load. These results suggest that OT and renal nerves are involved in renal vasodilation and natriuresis induced by acute plasma hypernatremia. The understanding of regulatory mechanisms activated both during obesity and during hyperosmolarity allows greater possibility development new therapeutic tools for hypertension prevention and treatment.